FRI0380 Patient preferences and difficulties concerning the home treatment options in systemic sclerosis (SSC). (15th June 2017) - Pagnotelli, B; Bruni, C; Randone, S Bellando; Guiducci, S; Lepri, G; Blagojevic, J; Rasero, L; Cerinic, M Matucci; Furst, DE
Abstract : Background: SSc patients suffer from Raynaud's phenomenon, hand skin hardening and scarring, digital ulcers, esophagus/gastric dysmotility, dysphagia and mucosal dryness. These symptoms significantly reduce patient's life autonomy and impair the capacity to handle their therapy usually made by different modalities of administration: oral, topical, inhalation, intramuscular, subcutaneous, intravenous, and rectal. Objectives: to investigate the methods of administration used by SSc patients, their preferred methods, their compliance to pharmacological therapy, and the difficulties that are encountered by the patients during pharmacotherapy. Methods: 2 questionnaires were prepared on an ad hoc basis. The first given to patients, the second to be filled out by the patient's physician. The first questionnaire comprised 25 questions to investigate the problems encountered by patients when taking their medications by correlating these with two validated activities indices: SHAQ-DI (activities of daily living) and the COCHIN scale (hand activities). The second questionnaire collected demographic and important SSc-related clinical information (eg.age, sex, disease duration, symptoms). 80 Ssc patients completed the questionnaires, maintaining anonymity. A "difficulty index" was also filled out, where: 0 = no difficulty to 4 = impossible to use or too difficult to use. Results: In particular, the dimension of the pills is problematic, and has identified a paradoxical situation because large pills are difficult to swallow (41, 25% patients who use pills) but at the same time small pills are difficult to pinch with the fingers (62, 25% patients who use pills). Conclusions: SSc patients experience significant problems in maintaining adherence to treatments due to difficulties in the use of blisters and bottles with children proof stoppers. Pills still remain the most preferred method of treatment. In conclusion, patients unanimously wished to avoid the use of blisters, defintively preferring bottles without the children proof stopper to make the treatment easier and provide a more independent life. Disclosure of Interest: None declared